The clinical and socioeconomic aspects of t-cell receptor excision circle based newborn screening for severe combined immunodeficiency in Southeast and East Asia - Yoo, Noelle; Kim, Seongjin; Kim, Jane; Ahn, Jong Gyun; Kang, Insoo; Shin, Junghee J. (Frontiers in Immunology, 2025)
Severe Combined Immunodeficiency (SCID) is a widely underdiagnosed congenital disease that is fatal by 2-years old if left untreated. Most cases of SCID are diagnosed from the prompting of family history while other cases are sporadic and have no indicators for diagnosis besides the onset of debilitating infections. T-cell Receptor Excision Circle Newborn Screening (TREC NBS) offers an accessible way of flagging for SCID and other T-cell lymphopenia; however, the test implementation rate is low, particularly in Asian countries. This review of the literature will explore the significance of TREC NBS for diagnosing SCID with a focus on the potential impact of widespread implementation on infant healthcare in Southeast and East Asian countries including South Korea, Japan, China, Mongolia, Taiwan, Malaysia, Singapore, and Thailand.